Hypersensitivity to intravenous succinate corticosteroids in patients with nonsteroidal anti-inflammatory drug-exacerbated respiratory disease - Taniguchi, Masami; Sato, Atsuhiko; Mita, Haruhisa (Frontiers in Allergy, 2023)
Although there are many case reports of asthma exacerbations with intravenous corticosteroids, especially hydrocortisone succinate, in nonsteroidal anti-inflammatory drug-exacerbated respiratory disease (N-ERD), the frequency and mechanism remain unclear. We hypothesized that N-ERD patients are potentially hypersensitive to succinates, especially succinate corticosteroids. The objective of this study was to determine the frequency and mechanism of succinate corticosteroids hypersensitivity in patients with N-ERD. Eleven patients with stable, moderate to severe N-ERD were tested with hydrocortisone sodium succinate (HCs), hydrocortisone sodium phosphate (HCp), methylprednisolone sodium succinate (MPSLs), prednisolone sodium succinate (PSLs), and chloramphenicol sodium succinate (CPs, without a steroidal chemical structure) at doses below the normal dose through intravenous administration using a single-blind test. As a comparison, seven patients with aspirin-tolerant asthma (ATA) also underwent an intravenous provocation test of HCs. The positive intravenous provocation test rates of HCs 100–500 mg, HCp 500 mg, MPSLs 80 mg, PSLs 20mg, and CPs 500 mg in N-ERD patients were 82% (9/11), 9% (1/11), 50% (5/10), 33% (1/3), and 86% (6/7), respectively. Most positive reactions began with a severe cough within 5 minutes of intravenous injection. The course of these hypersensitivity symptoms differed from those seen with the usual aspirin challenge test. The HCs 100–500 mg intravenous test was negative in all seven patients with ATA. In conclusion, patients with N-ERD have high rates of potential hypersensitivity to the succinate ester structure, which is not linked to the corticosteroid structure, but to the succinate ester structure. We hypothesized that the mechanism of hypersensitivity observed during rapid intravenous administration of succinate corticosteroids is mast cell activation via succinate receptor stimulation, rather than due to the corticosteroid itself.